Protein-losing enteropathy associated with thrombotic microangiopathic features revealing hirschsprung's disease in a child - Houda Nassih; Nahid Mahir; Fatima Taher; Rabiy El Qadiry (Wolters Kluwer Medknow Publications, 2021)
We report the case of a 4-year-old boy with protein-losing enteropathy, leading to severe malnutrition. Associated thrombotic microangiopathic features made diagnosis difficult and challenging.